(untitled) (Jurnal Sosial Ekonomi Pertanian, 2023)
West Aceh Regency has suboptimal land potential in the form of dry land which is quite large reaching 9,227.7 Ha. Expansion of harvest areas and increased productivity of rice and other foodstuffs are a must to meet food needs. The purpose of this study is to formulate a strategy to increase rice production on suboptimal land in West Aceh Regency. The research was conducted in East Woyla District, West Aceh Regency, Aceh Province. The research method uses qualitative descriptive analysis methods. The data used are primary data and secondary data. Sampling using purposive sampling technique. The sample amounted to 38 respondents, namely suboptimal land rice farmer that cultivate rice on dry land. Analyze strategy formulation using SWOT analysis. The results of the study are strategies in increasing rice production on suboptimal land is government intervention in socializing appropriate technology in cultivating rice on suboptimal land, as well as maintaining the availability of New Superior Varieties (VUB) seeds, fertilizers and agricultural machinery tools.